Solid acid catalyst and preparation and application thereof

Through the preparation and application of solid acid catalysts, the catalyst recovery and wastewater problems in the existing succinate synthesis process are solved, and efficient and environmentally friendly succinate synthesis is achieved.

CN119793431APending Publication Date: 2025-04-11SHANGHAI INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411980845.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

Smart Images

  • Figure CN119793431A_ABST
    Figure CN119793431A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fine chemical synthesis, in particular to a solid acid catalyst as well as preparation and application thereof. The preparation method comprises the following steps: firstly, uniformly mixing a tetrabutyl titanate solution and a tetraethoxysilane solution, then dropwise adding ammonia water to react, aging after the reaction is finished, and carrying out post-treatment to obtain a composite carrier TiO2-SiO2; dipping the composite carrier TiO2-SiO2 by using a metal salt solution, and sequentially carrying out evaporation drying, drying and roasting treatment to obtain the solid acid catalyst, the prepared solid acid catalyst has the advantages of being good in selectivity, high in catalytic activity, easy to reuse, high in stability and the like, and has the advantages of being easy and convenient to operate, high in reaction speed, high in yield and the like when being applied to the monomenthyl succinate synthesis process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fine chemical synthesis, and in particular to a solid acid catalyst and the preparation and application thereof. Background Art

[0002] Monomenthyl succinate has almost no aroma, only a cool and refreshing smell, with a lasting cool taste in the mouth and a good taste. It has a wide range of applications and can be used as a cooling agent in medicine, tobacco, beverages, daily chemicals, etc.

[0003] There are two main routes for the synthesis of monomenthyl succinate: direct esterification and acylation. The direct esterification method uses L-menthol and succinic acid as raw materials, and performs an esterification reaction under the action of an acidic catalyst to obtain the product. The disadvantage of this method is that the conversion rate is relatively low and waste acid is produced during the reaction process. The acylation method uses L-menthol and succinic anhydride to perform an acylation reaction under the action of a catalyst to obtain the product. This method has a high product yield and few by-products.

[0004] CN101823961A uses menthol and succinic anhydride to react at a certain temperature. After the reaction is completed, water is added for reflux reaction, and then ethyl acetate is extracted, the ethyl acetate is recovered, and then recrystallized with petroleum ether to obtain the product monomenthyl succinate.

[0005] CN105294436A uses DMAP as a catalyst and chloroform as a solvent. Menthol and succinic anhydride react at a certain temperature. After the reaction is completed, it is diluted with ethyl acetate and washed with 10% sodium carbonate. The water layer is acidified with dilute hydrochloric acid and extracted with ethyl acetate. The solvent is recovered to obtain the product monomenthyl succinate.

[0006] CN10738931B uses p-toluenesulfonic acid as a catalyst, and menthol and succinic anhydride react at a certain temperature to obtain a crude product of monomenthyl succinate, which is separated by silica gel column chromatography to obtain the product monomenthyl succinate.

[0007] US7247743B1 uses an alkaline catalyst (sodium carbonate or sodium acetate) or no catalyst to react menthol with succinic anhydride at a certain temperature to obtain a mixture containing 88.6% of monoester and 4.16% of diester, or a mixture containing 84.6% of monoester and 7.19% of diester.

[0008] It can be seen from the existing disclosed content that the synthesis of monomenthyl succinate is all carried out by acylation method, which can use acidic catalyst p-toluenesulfonic acid, basic catalyst sodium carbonate, sodium acetate or DMAP, which is a homogeneous catalyst, and has the problems of being unable to be recycled and producing waste water in post-treatment. In addition, DMAP is not easy to separate from the reaction solution (insoluble in water, soluble in organic solvents), and has toxicity and ammonia smell, and its retention in the product will cause quality problems of the product. However, if no catalyst is used, the reaction time will be long, and the diester content will be higher. Summary of the invention

[0009] In order to solve the problems of catalyst and post-treatment in the existing synthesis process of monomenthyl succinate, the purpose of the present invention is to provide a solid acid catalyst and its preparation and application. The solid acid catalyst prepared by the present invention has the advantages of good selectivity, high catalytic activity, easy reuse, high stability, etc., and is applied to the synthesis process of monomenthyl succinate, which has the advantages of simple operation, fast reaction speed, high yield, etc.

[0010] The purpose of the present invention can be achieved by the following technical solutions:

[0011] The first object of the present invention is to provide a method for preparing a solid acid catalyst, comprising the following steps:

[0012] (S1) mixing a tetrabutyl titanate solution and a ethyl orthosilicate solution, then dropping ammonia water to react, and aging and post-treating after the reaction to obtain a composite carrier TiO2-SiO2;

[0013] (S2) impregnating the composite carrier TiO2-SiO2 prepared in step (S1) with a metal salt solution, and then evaporating, drying, and calcining the mixture to obtain a solid acid catalyst;

[0014] Wherein, the metal salt solution is selected from one of zirconium salt, cerium salt, tin salt or zinc salt.

[0015] In one embodiment of the present invention, in step (S1), the amount of tetrabutyl titanate and ethyl orthosilicate added ensures that the molar ratio of titanium to silicon is 1:1 (the surface area and pore volume of the composite carrier TiO2-SiO2 are the largest, and more active centers can be provided);

[0016] Ammonia water is added dropwise until the solution pH is 9-10;

[0017] During the reaction, the temperature is 25-30°C and the reaction time is 2-3h;

[0018] During the aging process, the temperature is -5 to -10°C and the time is 5 to 10 hours.

[0019] In one embodiment of the present invention, the tetrabutyl titanate solution is an ethanol solution of tetrabutyl titanate, and the ethyl orthosilicate solution is an ethanol solution of ethyl orthosilicate;

[0020] The mass concentration of the ammonia water is 20-25%.

[0021] In one embodiment of the present invention, in step (S1), the post-treatment is specifically as follows: after the aging is completed, the precipitated solid is filtered, washed, dried, roasted, ground, and sieved in sequence.

[0022] In one embodiment of the present invention, during the drying process, the temperature is 110-120°C;

[0023] During the calcination process, the temperature is 450-550°C (preferably, the temperature is 500°C) and the time is 4-5h;

[0024] During the screening process, the mesh size of the screen is 20 to 40 meshes.

[0025] In one embodiment of the present invention, in step (S2), the zirconium salt is selected from one of zirconium oxynitrate dihydrate or zirconium oxychloride octahydrate;

[0026] The cerium salt is selected from cerium nitrate;

[0027] The tin salt is selected from tin tetrachloride;

[0028] The zinc salt is selected from zinc sulfate or zinc chloride.

[0029] In one embodiment of the present invention, in step (S2), when the metal salt is a zirconium salt, the loading amount of zirconium is 12 to 18 wt%;

[0030] When the metal salt is a cerium salt, the loading amount of cerium is 12 to 18 wt %;

[0031] When the metal salt is a tin salt, the loading amount of tin is 14.5 to 20.5 wt %;

[0032] When the metal salt is a zinc salt, the loading amount of zinc is 8.5 to 14.5 wt %.

[0033] In one embodiment of the present invention, when the metal salt is a zirconium salt, the loading amount of zirconium is 16 wt %;

[0034] When the metal salt is a cerium salt, the loading amount of cerium is 16 wt %;

[0035] When the metal salt is a tin salt, the loading amount of tin is 18.5 wt%;

[0036] When the metal salt is a zinc salt, the loading amount of zinc is 12.5 wt %.

[0037] In one embodiment of the present invention, in step (S2), during the impregnation process, the impregnation time is 10 to 15 hours;

[0038] During the drying process, the temperature was 110°C;

[0039] During the calcination process, the temperature is 700-800° C. (preferably, the temperature is 750° C.) and the time is 4-5 hours.

[0040] The second object of the present invention is to provide a solid acid catalyst, characterized in that the solid acid catalyst is prepared by the above method, with TiO2-SiO2 as the composite carrier, and the active component is zirconium, cerium, tin or zinc.

[0041] The third object of the present invention is to provide an application of a solid acid catalyst in the preparation of monomenthyl succinate, wherein the solid acid catalyst is a solid acid catalyst.

[0042] The fourth object of the present invention is to provide a method for preparing monomenthyl succinate, comprising the following steps:

[0043] (A1) heating and melting succinic anhydride and a solid acid catalyst, and then mixing and reacting with menthol to obtain an intermediate product;

[0044]

[0045] (A2) dissolving the intermediate product of step (A1) and filtering to recover the solid acid catalyst, heating the reaction solution for reaction and then dripping water to continue the reaction, and performing post-treatment after the reaction to obtain monomenthyl succinate.

[0046] In one embodiment of the present invention, in step (A1), the molar ratio of succinic anhydride to menthol is 1 to 1.6:1; the mass ratio of the solid acid catalyst to menthol is 1 to 4:100 (preferably, the mass ratio of the solid acid catalyst to menthol is 1:50); during the reaction, the temperature is 110 to 140° C., and the reaction time is 2 to 5 hours;

[0047] In one embodiment of the present invention, in step (A1), the reaction is continuously stirred at a speed of 400 to 600 rpm, preferably, at a speed of 500 rpm;

[0048] The menthol is selected from one of D-menthol, L-menthol or D,L-menthol. Preferably, the menthol is L-menthol.

[0049] In step (A2), during the reaction, the temperature is 55-60° C. and the reaction time is 2.5-3 h.

[0050] In one embodiment of the present invention, in step (A2), the intermediate product is dissolved in a solvent selected from one of cyclohexane, toluene or heptane;

[0051] The solid acid catalyst can be reused after being recovered, and can be restored to activity by calcination (temperature of 750° C., time of 4 to 5 hours) after its activity decreases.

[0052] In one embodiment of the present invention, in step (A2), the post-treatment is specifically as follows:

[0053] After the reaction is completed, the aqueous layer is separated, the water is evaporated to dryness, and the succinic acid is recovered; the solvent is recovered from the organic layer, and high vacuum reduced pressure distillation is performed to obtain monomenthyl succinate.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] (1) The solid acid catalyst prepared by the present invention has the advantages of good product selectivity, high raw material conversion rate, and easy reuse.

[0056] (2) In the acylation reaction of the present invention, a solid acid catalyst is used, and the dispersion of TiO2 on the surface of SiO2 can enhance the MO x The interaction between metal oxide and composite support improves the MO x The dispersion threshold on the composite support surface improves MO x The dispersed state increases the number of acid centers on the surface of the solid acid catalyst, enhances the acidity, and further improves the reaction activity of the solid acid catalyst; in addition, high-temperature calcination is used, and the acid centers are mainly L-acid, which is beneficial to the synthesis of monomenthyl succinate, because L-menthol is a secondary alcohol and is not easy to dehydrate in an L-acid environment; due to the high catalytic activity and good thermal stability of the solid acid catalyst, it is superior to catalysts such as p-toluenesulfonic acid, sodium carbonate, sodium acetate or DMAP in the synthesis of L-menthyl succinate.

[0057] (3) In the post-treatment of the acylation reaction of the present invention, by adding water to hydrolyze at a certain temperature, the excess succinic anhydride can be completely converted into succinic acid and enter the water layer, thereby recovering the raw materials and facilitating the purification of the product.

[0058] (4) The present invention uses a solid acid catalyst to prepare succinic acid monoester, which is easy to operate, has a simple process route, and is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is the EDS graph of the solid acid catalyst (16% Zr / TS-1) prepared in Example 1. DETAILED DESCRIPTION

[0060] The present invention is described in detail below with reference to specific embodiments.

[0061] In the following examples, the gas phase column used is KB-50 30m*0.32mm*1.00μm, and the analysis method integration method uses the area normalization method; unless otherwise specified, the reagents used are commercially available reagents, and the detection means and methods used are conventional detection means and methods in the art.

[0062] Example 1

[0063] This embodiment provides a method for preparing a composite carrier TiO2-SiO2, which specifically includes the following steps:

[0064] (1) dissolving 34.0 g of tetrabutyl titanate in 310 g of ethanol to obtain a tetrabutyl titanate ethanol solution;

[0065] Dissolve 15.0 g of ethyl silicate (containing 40% SiO2) in 10 g of ethanol to obtain an ethyl silicate ethanol solution;

[0066] (2) Under stirring, the tetrabutyl titanate ethanol solution prepared in step (1) and the ethyl silicate ethanol solution are uniformly mixed, and then 25 wt % ammonia water is added dropwise until the pH reaches 9-10, and the reaction temperature is controlled at 30° C. After the addition, stirring is continued for 2 h, and then the temperature is lowered to -5° C. for aging treatment for 8 h;

[0067] (3) After step (2), the reaction solution was filtered, the filter cake was washed with distilled water, and then the filter cake was dried at 120°C for 6 hours, and then calcined at 600°C for 6 hours. After grinding, it was sieved with a 30-mesh sieve to obtain a composite carrier TiO2-SiO2 (n(Ti) / n(Si)=1:1), hereinafter referred to as TS-1.

[0068] Example 2

[0069] This embodiment provides a method for preparing a solid acid catalyst (16% Zr / TS-1), comprising the following steps:

[0070] (S1) dissolving 5.59 g of zirconium oxynitrate dihydrate in 30.0 g of distilled water to obtain a zirconium oxynitrate aqueous solution;

[0071] (S2) 10.0 g of TS-1 prepared in Example 1 was added to the zirconium oxynitrate aqueous solution under stirring (500 rpm), immersed for 12 h, most of the water was removed by rotary evaporation, dried at 110° C. for 4 h, and calcined at 750° C. for 5 h to obtain a solid acid catalyst: 16% Zr / TS-1 (wherein 16% Zr means that the zirconium loading is 16% of the mass of the solid acid catalyst), and its EDS graph is as follows: Figure 1 shown.

[0072] Example 3

[0073] This embodiment provides a method for preparing a solid acid catalyst (12% Zr / TS-1). Compared with Example 2, this embodiment only changes the loading amount of zirconium, and the rest is the same as Example 2.

[0074] Example 4

[0075] This embodiment provides a method for preparing a solid acid catalyst (14% Zr / TS-1). Compared with Embodiment 2, this embodiment only changes the loading amount of zirconium, and the rest is the same as Embodiment 2.

[0076] Example 5

[0077] This embodiment provides a method for preparing a solid acid catalyst (18% Zr / TS-1). Compared with Example 2, this embodiment only changes the loading amount of zirconium, and the rest is the same as Example 2.

[0078] Example 6

[0079] This embodiment provides a method for preparing a solid acid catalyst (12% Ce / TS-1), comprising the following steps:

[0080] (S1) dissolving 3.78 g of cerium tetranitrate in 30.0 g of distilled water to obtain a cerium tetranitrate aqueous solution;

[0081] (S2) Add 10.0 g of TS-1 prepared in Example 1 under stirring (rotation speed is 500 rpm), soak for 12 hours, remove most of the water by rotary evaporation, dry at 110° C. for 4 hours, and calcine at 750° C. for 5 hours to obtain a solid acid catalyst: 12% Ce / TS-1 (wherein, 12% Ce means that the cerium loading is 12% of the mass of the solid acid catalyst).

[0082] Example 7

[0083] This embodiment provides a method for preparing a solid acid catalyst (14% Sn / TS-1), comprising the following steps:

[0084] (S1) dissolving 3.57 g of tin tetrachloride in 30.0 g of distilled water to obtain a tin tetrachloride aqueous solution;

[0085] (S2) 10.0 g of TS-1 prepared in Example 1 was added under stirring (rotation speed of 500 rpm), immersed for 12 h, most of the water was removed by rotary evaporation, dried at 110° C. for 4 h, and calcined at 750° C. for 5 h to obtain a solid acid catalyst: 14% Sn / TS-1 (wherein, 14% Sn means that the tin loading is 14% of the mass of the solid acid catalyst).

[0086] Example 8

[0087] This embodiment provides a method for preparing a solid acid catalyst (18% Zn / TS-1), comprising the following steps:

[0088] (S1) dissolving 9.99 g of zinc nitrate hexahydrate in 35.0 g of distilled water to obtain a zinc nitrate aqueous solution;

[0089] (S2) 10.0 g of TS-1 prepared in Example 1 was added under stirring (rotation speed of 500 rpm), immersed for 12 h, most of the water was removed by rotary evaporation, dried at 110° C. for 4 h, and calcined at 750° C. for 5 h to obtain a solid acid catalyst: 18% Zn / TS-1 (wherein, 18% Zn means that the zinc loading is 18% of the mass of the solid acid catalyst).

[0090] Example 9

[0091] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0092] Succinic anhydride and a solid acid catalyst (12% Zr / TS-1 prepared in Example 3, 14% Zr / TS-1 prepared in Example 4, 16% Zr / TS-1 prepared in Example 2, and 18% Zr / TS-1 prepared in Example 5, respectively) were added to a reactor equipped with a stirrer, a thermometer and a drying tube. The reaction temperature was 120° C. L-menthol was added dropwise and the reaction was continued after the addition was completed. The entire reaction time was 3 hours. The results are shown in Table 1.

[0093] In this embodiment, the molar ratio of succinic anhydride to L-menthol is 1.2:1, and the weight ratio of the solid acid catalyst to L-menthol is 1:50.

[0094] Table 1 Summary of product contents

[0095] catalyst L-Menthol (%) Monomenthyl succinate (%) Dimenthyl succinate (%) 12%Zr / TS-1 1.2 98.4 0.4 14% Zr / TS-1 0.8 98.7 0.5 16%Zr / TS-1 0.3 99.1 0.6 18% Zr / TS-1 0.5 98.9 0.6

[0096] Example 10

[0097] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0098] Succinic anhydride and a solid acid catalyst (16% Zr / TS-1 prepared in Example 2, 12% Ce / TS-1 prepared in Example 6, 14% Sn / TS-1 prepared in Example 7, and 18% Zn / TS-1 prepared in Example 8, respectively) were added to a reactor equipped with a stirrer, a thermometer and a drying tube. The reaction temperature was 120° C. L-menthol was added dropwise and the reaction was continued after the addition was completed. The entire reaction time was 3 hours. The results are shown in Table 2.

[0099] Among them, the one without adding catalyst was used as the control group;

[0100] In this embodiment, the molar ratio of succinic anhydride to L-menthol is 1.2:1, and the weight ratio of the solid acid catalyst to L-menthol is 1:50.

[0101] Table 2 Summary of product contents

[0102] catalyst L-Menthol (%) Monomenthyl succinate (%) Dimenthyl succinate (%) No catalyst 25.3 74.5 0.2 16%Zr / TS-1 0.3 99.1 0.6 12%Ce / TS-1 0.9 98.0 1.0 14%Sn / TS-1 2.3 96.0 1.5 18%Zn / TS-1 0.5 98.7 0.8

[0103] Embodiment 11

[0104] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0105] Succinic anhydride and the solid acid catalyst 16% Zr / TS-1 prepared in Example 2 were added to a reactor equipped with a stirrer, a thermometer and a drying tube. The reaction temperatures were 110° C., 120° C., 130° C. and 140° C., respectively. L-menthol was added dropwise and the reaction was continued after the addition. The entire reaction time was 3 h. The results are shown in Table 3.

[0106] In this embodiment, the molar ratio of succinic anhydride to L-menthol is 1.2:1, and the weight ratio of the solid acid catalyst to L-menthol is 1:50.

[0107] Table 3 Summary of product contents

[0108] temperature L-Menthol (%) Monomenthyl succinate (%) Dimenthyl succinate (%) 110℃ 14.25 85.6 0.30 120℃ 0.3 99.1 0.60 130℃ 0.3 95.6 0.80 140℃ 0.2 93.8 1.25

[0109] Example 12

[0110] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0111] Succinic anhydride and the solid acid catalyst 16% Zr / TS-1 prepared in Example 2 were added to a reactor equipped with a stirrer, a thermometer and a drying tube, heated to 120° C., L-menthol was added dropwise, and the reaction was continued after the addition. The entire reaction time was 3 hours. The results are shown in Table 4.

[0112] In this embodiment, the molar ratio of succinic anhydride to L-menthol is 1.2:1, and the weight ratio of the solid acid catalyst to L-menthol is 1:50.

[0113] Table 4 Summary of product contents

[0114] Reaction time L-Menthol (%) Monomenthyl succinate (%) Dimenthyl succinate (%) 2h 5.0 94.5 0.50 3h 0.3 99.1 0.60 4h 0.3 97.6 0.65 5h 0.2 96.4 0.84

[0115] Example 13

[0116] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0117] Succinic anhydride and the solid acid catalyst 16% Zr / TS-1 prepared in Example 2 were added to a reactor equipped with a stirrer, a thermometer and a drying tube. The reaction temperature was 120° C. L-menthol was added dropwise and the reaction was continued after the addition. The entire reaction time was 3 hours. The results are shown in Table 5.

[0118] In this embodiment, the molar ratios of succinic anhydride to L-menthol are 1:1, 1.2:1, 1.4:1, and 1.6:1, respectively, and the weight ratio of the solid acid catalyst to L-menthol is 1:50.

[0119] Table 5 Summary of product contents

[0120] Succinic Anhydride: L-Menthol L-Menthol (%) Monomenthyl succinate (%) Dimenthyl succinate (%) 1:1 1.6 96.4 2.00 1.2:1 0.3 99.1 0.60 1.4:1 0.2 98.7 0.51 1.6:1 0.1 98.5 0.51

[0121] Embodiment 14

[0122] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0123] In a reactor equipped with a stirrer, a thermometer and a drying tube, 88.0 g (0.88 mol) of succinic anhydride and 2.5 g of the solid acid catalyst prepared in Example 2: 16% Zr / TS-1 were added, heated to 120° C., 124.8 g (0.80 mol) of L-menthol was added dropwise, and the reaction was continued after the addition was completed for 3 h to obtain a reaction solution;

[0124] The reaction solution was cooled to 60°C, 82.0 g of water was added dropwise, and the hydrolysis was continued for 1.0 h. The solution was cooled to room temperature and extracted with 120 ml of cyclohexane to separate the aqueous layer and the organic layer.

[0125] Water layer: water and succinic acid. After the water is evaporated to dryness, succinic acid (12.0 g of white solid) is recovered.

[0126] Organic layer: cyclohexane, L-menthol, monomenthyl succinate and dimenthyl succinate; cyclohexane is recovered and subjected to high vacuum decompression distillation (vacuum degree: 0.2-0.3 mmHg) to obtain the product, and fraction 1 (L-menthol) and fraction 2 (monomenthyl succinate) are obtained in sequence. The specific results are shown in Table 6.

[0127] Table 6 Summary of product contents

[0128] L-Menthol Succinic anhydride Monomenthyl succinate Dimenthyl Succinate Reaction liquid content 0.29% 2.4% 96.7% 0.59% After washing the reaction solution 0.30% 0.0% 99.1% 0.60% Fraction 1, 5.0 g 12.0% 88.0% Fraction 2, 201.1 g 0.0% 99.9% 0.1% In bottle, 10.0g 0.0% 87.4% 12.4%

[0129] Embodiment 15

[0130] This embodiment provides a method for preparing monomenthyl succinate, comprising the following steps:

[0131] Succinic anhydride and the solid acid catalyst 16% Zr / TS-1 prepared in Example 2 were added to a reactor equipped with a stirrer, a thermometer and a drying tube. The reaction temperature was 120° C. L-menthol was added dropwise and the reaction was continued after the addition. The entire reaction time was 3 h. The solid acid catalyst was reused 5 times. The results are shown in Table 7.

[0132] In this embodiment, the molar ratio of succinic anhydride to menthol is 1.2:1, and the weight ratio of the solid acid catalyst to menthol is 1:50.

[0133] Table 7 Summary of product contents

[0134] Repetitions L-Menthol (%) Monomenthyl succinate (%) Dimenthyl succinate (%) 1 0.3 99.1 0.60 2 0.7 98.7 0.60 3 0.8 98.6 0.55 4 1.2 98.2 0.50 5 2.6 96.8 0.48

[0135] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a solid acid catalyst, characterized in that: The following steps are involved: (S1) mixing a tetrabutyl titanate solution and a ethyl orthosilicate solution, then dropping ammonia water to react, and aging and post-treating after the reaction to obtain a composite carrier TiO2-SiO2; (S2) impregnating the composite carrier TiO2-SiO2 prepared in step (S1) with a metal salt solution, and then evaporating, drying, and calcining the mixture to obtain a solid acid catalyst; Wherein, the metal salt solution is selected from one of zirconium salt, cerium salt, tin salt or zinc salt.

2. The method for preparing a solid acid catalyst according to claim 1, characterized in that: In step (S1), the molar ratio of titanium to silicon is 1:1; Ammonia water is added dropwise until the solution pH is 9-10; During the reaction, the temperature is 25-30°C and the reaction time is 2-3h; During the aging process, the temperature is -5 to -10°C and the time is 5 to 10 hours.

3. The method for preparing a solid acid catalyst according to claim 1, characterized in that: In step (S1), the post-treatment is specifically as follows: after the aging is completed, the precipitated solid is filtered, washed, dried, roasted, ground, and sieved in sequence.

4. The method for preparing a solid acid catalyst according to claim 1, characterized in that: In step (S2), the zirconium salt is selected from one of zirconium oxynitrate dihydrate or zirconium oxychloride octahydrate; The cerium salt is selected from cerium nitrate; The tin salt is selected from tin tetrachloride; The zinc salt is selected from zinc sulfate or zinc chloride.

5. The method for preparing a solid acid catalyst according to claim 1, characterized in that: In step (S2), when the metal salt is a zirconium salt, the loading amount of zirconium is 12 to 18 wt %; When the metal salt is a cerium salt, the loading amount of cerium is 12 to 18 wt %; When the metal salt is a tin salt, the loading amount of tin is 14.5 to 20.5 wt %; When the metal salt is a zinc salt, the loading amount of zinc is 8.5 to 14.5 wt %.

6. The method for preparing a solid acid catalyst according to claim 2, characterized in that: In step (S2), during the immersion process, the immersion time is 10 to 15 hours; During the drying process, the temperature was 110°C; During the roasting process, the temperature is 700-800°C and the time is 4-5 hours.

7. A solid acid catalyst, characterized in that The solid acid catalyst is prepared by the method according to any one of claims 1 to 6.

8. Use of a solid acid catalyst in the preparation of monomenthyl succinate, characterized in that: The solid acid catalyst is the solid acid catalyst according to claim 7.

9. A method for preparing monomenthyl succinate, characterized in that: The following steps are involved: (A1) heating and melting succinic anhydride and the solid acid catalyst according to claim 7, and then mixing and reacting with menthol to obtain an intermediate product; (A2) dissolving the intermediate product of step (A1) and filtering to recover the solid acid catalyst, heating the reaction solution for reaction and then dripping water to continue the reaction, and performing post-treatment after the reaction to obtain monomenthyl succinate.

10. The method for preparing monomenthyl succinate according to claim 9, characterized in that: In step (A1), the molar ratio of succinic anhydride to menthol is 1 to 1.6:1; the mass ratio of the solid acid catalyst to menthol is 1 to 4:100; during the reaction, the temperature is 110 to 140° C. and the reaction time is 2 to 5 hours; In step (A2), during the reaction, the temperature is 55-60°C.

Citation Information

Patent Citations

  • Preparation method of supported sulfuric acid catalyst

    CN106000426A

  • Preparation method of mesoporous TiO2-SiO2 loaded sulfonated metal phthalocyanine catalyst

    CN107051584A

  • MnWOx / TiO2-SiO2 denitration catalyst as well as preparation and application thereof

    CN107583640A

  • Mesoporous solid acid catalyst as well as preparation method and application thereof

    CN114289042A

  • Modified molecular sieve catalyst as well as preparation method and application thereof

    CN116764673A